METACOGNITION AND LEARNING COMMITMENT OF GRADE 12 LEARNERS IN THE PHILIPPINES - Llamelo, Gina L. (President University, 2024)
This study aimed to investigate the degree of metacognition and the level of learning commitment among 387 Grade 12 learners in the Philippines. The context of the study included an examination of metacognitive aspects such as self-monitoring, self-regulation, and reflective practices, as well as curricular and non-curricular school engagements as measures of learning commitment. Utilizing a correlational design, data were collected to explore relationships between these variables. The analysis indicated a high level of metacognition in terms of self-monitoring, self-regulation, and reflective practices among the learners. Similarly, a high level of commitment to learning was observed, both in curricular and non-curricular engagements. No significant differences were found in the degree of metacognition when considering sex and residential location, but significant differences were noted concerning the respondents’ strand, parents' highest educational attainment, and parents’ occupation. Similarly, no significant differences in learning commitment were found concerning sex, parents’ highest educational attainment, parents' occupation, and residential location, but differences were significant with respect to the respondents’ strand. A significant relationship was identified between the degree of metacognition and the level of learning commitment. The findings imply that enhancing metacognitive skills may foster greater commitment to learning among students, highlighting the importance of tailored educational strategies that address various demographic factors.